2015
DOI: 10.11613/bm.2015.020
|View full text |Cite
|
Sign up to set email alerts
|

Method evaluation study of a new generation of vitamin D assays

Abstract: IntroductionRecently several diagnostic manufacturers have launched new 25-hydroxy-vitamin D (25[OH]D) assays, which are aligned to the National Institute of Standards and Technology (NIST) Standard Reference Materials (SRM) (NIST, Gaithersburg, Maryland). The aim of this study was to compare the performance of one liquid chromatography-tandem mass spectrometry (LC-MS/MS) method, one enzyme linked immunosorbent assay (ELISA), and one recalibrated and previous version of a chemiluminescence immunoassay (CLIA).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 29 publications
1
48
1
1
Order By: Relevance
“…The mass screening of the VD deficiency, which is based on the blood 25(OH)D 3 quantification, in neonatal infants is important for the early detection, diagnosis and health risk assessment of several diseases (Enko, Kriegshäuser, Stolba, Worf, & H‐Baumann, ; Gervasoni, Cocci, Zuppi, & Persichilli, ). A permanently charged Cookson‐type reagent called SecoSET™ (Figure h), which is commercially available from Novilytic as the VD assay kit, was applied to the determination of plasma 25(OH)D 3 on the card (dried blood spot).…”
Section: Application Of Cookson‐type Reagents To Analysis Of Vd Compomentioning
confidence: 99%
“…The mass screening of the VD deficiency, which is based on the blood 25(OH)D 3 quantification, in neonatal infants is important for the early detection, diagnosis and health risk assessment of several diseases (Enko, Kriegshäuser, Stolba, Worf, & H‐Baumann, ; Gervasoni, Cocci, Zuppi, & Persichilli, ). A permanently charged Cookson‐type reagent called SecoSET™ (Figure h), which is commercially available from Novilytic as the VD assay kit, was applied to the determination of plasma 25(OH)D 3 on the card (dried blood spot).…”
Section: Application Of Cookson‐type Reagents To Analysis Of Vd Compomentioning
confidence: 99%
“…On the other hand Clinical and Laboratory Standards Institute (CLSI) recommends plotting differences against the reference method. Therefore, differences between values from comparative immunoassays and the reference method against the reference method value were displayed in the difference plots according to CLSI recommendations (Enko, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high percentage (51-62%) of cross-reactivity with 3-epi-25-hydroxyvitamin D, the enzymatic method seems to be unsuitable for measurements of vitamin D in paediatric samples [11]. A recent study by Stepman et al showed that 3-epi metabolites could be identified not only in children but also in adults, reaching up to [13,17]. Evaluation of mean bias was achieved by Bland-Altman calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-reactivity with 24,25(OH) 2 or 3-epimers in some immunoassays can contribute to overestimation of 25(OH)D and consequently lead to misclassification of vitamin D status. The percentage of 3-epi metabolite was estimated by Bailey et al to be 11% in pregnant women and up to 25% in infants [9,13]. The "gold standard" for adequate separation of 3-epimers and 24,25(OH)D metabolites, which is the function of LC-MS/MS, cannot be commonly implemented because of economical and organisational reasons.…”
Section: Introductionmentioning
confidence: 99%